IMPLEMENTASI STIMULATION MAT UNTUK OPTIMALISASI PERKEMBANGAN ANAK DI DESA NGALANG KECAMATAN GEDANGSARI GUNUNG KIDUL - Endah Puji Puji Astuti; Tri Sunarsih (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
Implementation of a Stimulation Mat for Optimizing Child Development in Ngalang Village, Gedangsari District, Gunung KidulBackground: Based on the results of the researcher's survey in the initial study conducted in Ngalang Village on March 3, 2020, many village Posyandu and PAUD did not have parental education activities if there was only a form of activity in the form of seminars. There are no specific media used for parenting education activities, including media for stimulating children's growth, which should be urgent in a PAUD or Posyandu. Objectives: try to make a medium in the form of a stimulation mat or development mat for teachers and cadres so that they can learn about children's development and provide stimulation independently through the development mat. Methods: This type of research is development (research and development). The development procedure that the researchers used in developing the Stimulation Mat media were (1) initial research and information; (2) planning; (3) development of initial product formats; (4) initial trials; (5) product revision; (6) field trials; (7) product revision; (8) field testing; (9) final product revision; (10) dissemination and implementation. Results: 80% of the results of the pediatric specialist production (very feasible/good), the results of the assessment of media experts 96% (very feasible / very good), the results of the trial at Keder stated very good / very feasible as many as 18 (62.1%) cadres and 6 (20.7%) stated that it was good/feasible and as many as 79.6% were tested for under-fives. Conclusion: The learning media development mat is suitable for use as a medium for stimulation and early detection of child development. The use of the Development Mat media is effective in introducing the stages of a child's development